Bio-Optical Properties of Two Neigboring Coastal Regions of Tropical Northern Australia: The Van Diemen Gulf and Darwin Harbour - Blondeau-Patissier, David; Schroeder, Thomas; Clementson, Lesley A.; Brando, Vittorio E.; Purcell, Diane; Ford, Phillip; Williams, David K.; Doxaran, David; Anstee, Janet; Thapar, Nandika; Tovar-Valencia, Miguel (Frontiers in Marine Science, 2017)
This study focuses on the seasonal and spatial characterization of inherent optical properties and biogeochemical concentrations in the Van Diemen Gulf and Darwin Harbour, two neighboring tropical coastal environments of Northern Australia that exhibit shallow depths (~20 m), large (>3 m) semi-diurnal tides, and a monsoonal climate. To gain insight in the functioning of these optically complex coastal ecosystems, a total of 23 physical, biogeochemical, and optical parameters were sampled at 63 stations during three field campaigns covering the 2012 wet and dry seasons, and the 2013 dry season. The total light absorption budget in the Van Diemen Gulf was dominated by non-algal particles (aNAP; >45%) during the dry season (May–October) and colored dissolved organic matter (aCDOM; 60%) during the wet season (November–April). The combined absorption by aNAP and aCDOM generally exceeded ~80% of the total absorption budget from 400 to 620 nm, with phytoplankton, aPhy, accounting for <20%. In Darwin Harbour, where only the dry season conditions were sampled, the total absorption budget was dominated by an equivalent contribution of aCDOM, aNAP, and phytoplankton. The major processes explaining the seasonal variability observed in the Van Diemen Gulf are resuspension from seasonal south-easterly trade winds in combination with the tidal energy and shallow bathymetry during the dry season months, and mostly terrestrial river runoff during the monsoon which discharge terrestrial CDOM from the surrounding wetlands. Due to light-limited conditions all year round, the particulate scattering coefficient [bp(555)] contributed significantly (90%) to the beam attenuation coefficient c(555), thus strongly limiting phytoplankton growth (Chlorophyll a ~1 mg.m−3). Spatially, the Van Diemen Gulf had higher total suspended solids and nutrient concentrations than Darwin Harbour, with dissolved organic carbon and aCDOM subjected to photobleaching during the dry season. Key bio-optical relationships derived from this comprehensive set of parameters, the first ever to be collected in this tropical coastal environment, were successfully used for a region-specific seasonal parameterization a region-specific seasonally parameterized ocean color algorithm. Challenges related to the parameterization, and the use, of ocean color remote sensing algorithms for these optically complex waters are discussed.